SMART Integrated Circuit Design and Methodology - Noulis, Thomas; Psychalinos, Costas; Hatzopoulos, Alkis (River Publishers, 2023)
This book describes advanced flows and methodologies for the design and implementation of system-on-chip (SoC). It is written by a mixture of industrial experts and key academic professors and researchers. The intended audience is not only students but also engineers with system-on-chip and semiconductor background currently working in the semiconductor industry. Integrated Circuits are available in every electronic product, especially in emerging market segments such as 5G mobile communications, autonomous driving, fully electrified vehicles, and artificial intelligence. These product types require real-time processing at billions of operations per second. The development design cycle time is driving costs and time to market more than ever before. The traditional design methodologies have reached their limits and innovative solutions are essential to serve the emerging SoC design challenges. In the framework of the Circuit and System Society (CASS) Outreach Initiative 2022 call, the SMART Integrated Circuits design methodology ⁰́₃ named SMARTIC ⁰́₃ Seasonal School was performed in November 2022, in Thessaloniki (Greece). Features: ⁰́Ø Core analog circuits of any system of chip, such as high-performance rectifiers and filters, are addressed in detail, together with their respective design methodology. ⁰́Ø New advanced methodologies towards design cycle speed up based on machine learning and artificial intelligence applications. ⁰́Ø Advanced analog design methodology based on gm/Id and lock up tables. A powerful flow for enabling fast time to market analog circuit design focusing on baseband circuits. ⁰́Ø More exotic methodologies and applications with focus on digital-based analog processing in nanoscale CMOS ICs and the design and development of depleted monolithic active pixel sensors for high-radiation applications, together with all the respective challenges of this application.
Description based upon print version of record.
Keywords: Systems on a chip -- Design and construction.; elektronické knihy; electronic books